Political and Legal Perspectives of the Ratification of the Next Generation EU in Poland - Serowaniec, Maciej; Przychodzki, Michał; Woźniakowski, Tomasz (PRAWO i WIĘŹ, 2025)
This study aims to present the nature of international organisations' treaty-making powers, with a particular focus on their implied powers. While the powers expressly granted in the constitutional instrument of a given international organisation are clear, implied powers — a special category of attributed powers — require a complex implication process based on uncertain foundations and therefore attract far more criticism. Nevertheless, implication of powers allows for a more dynamic interpretation of attributed powers, which is especially important given the constantly evolving activities of international organisations in areas beyond the scope of their statutes. Due to the unique nature of this category of treaty-making powers and the associated questions concerning their basis and implication, the author considers this issue within the broader context of international organisations' capacities and powers.